TANGGUNGJAWAB PERS NASIONAL SEBAGAI SUBJEK HUKUM PIDANA DALAM PERSPEKTIF TANGGUNGJAWAB KORPORASI - Raden Muhamad Ibnu Mazjah (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2019)
Every legal subject who commits a crime can be subject to criminal liability as long as it meets the element of error. No exception to criminal liability against the press which is an instrument in expressing opinions and expression. Based on the system of criminal law, criminal acts carried out using press instruments are included in the provisions concerning defamation and humiliation either through writing and or drawing. The emphasis of the criminal act of the press is on the aspect of publication. Birth of Law No. 40 of 1999 which places the national press as a legal entity should have implications for the accountability of the press to the concept of corporate responsibility. This is a reference given that in carrying out the duties and functions of the press, the corporation is the carrier of rights and obligations that have goals as well as the controlling parties of a national press company. The position of the person of the press or journalist is the party who runs the activity or receives orders from the corporation. In practice, journalists are often placed as legal subjects who are liable for the consequences of a criminal act in carrying out their journalistic duties. This happens because the regulation of corporate criminal liability regarding press cases does not manifest explicitly in Law No. 40 of 1999. The existence of individual accountability arrangements (naturlijke persoon) based on geen teachings straf zonder schuld as the teachings of accountability in the Criminal Code in turn become a threat to journalists in carrying out their work. Scientific writing uses normative legal research methods. In addition to relying on the law approach, this research also uses a conceptual approach, namely by presenting the doctrine of corporate responsibility and superior respondeat doctrine. In practice, the freedom of the press for journalists ultimately depends very much on the attitudes and objectives of the national press company where they are playing. This writing finally brings a concept of the criminal responsibility of the national press that adheres to the criminal responsibility of the corporation in the form of criminal administration, so that it further guarantees the implementation of press freedom because it no longer accommodates imprisonment for the press or journalists.